Sistem Deteksi Dini Bencana Tanah Longsor Berbasis 3D WebGIS - Deny Prasetia Taruma Wardana; Fatwa Ramdani; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Kota Batu is threated by landslide disaster, based on data from BPBD Kota Batu in the period of January 1, 2016 to July 31, 2016, there have been 39 landslide events, with the value of material loss reached Rp. 2,836,000,000,00. Early detection system of landslide disaster that has been installed BPBD Kota Batu currently can not work optimally. As the result the sistem is not appropriated. To overcome these problems, this research proposes a solution of early landslide detection system based on 3D landslide WebGIS with real time monitoring system and spatial data visualization, in order to anticipate landslide disaster. Stage of software development using prototype model to guarantee software quality according to requirement of BPBD Kota Batu. Implementation phase is done by extraction of DEM data, then processing spatial data result of onscreen digitation BALITBANGDA Kota Batu, extraction of survey result data, building digitation, building 3D Map, and doing 3D Map visualization into WebGIS. The test method uses unit testing and sensor accuracy. Unit testing results show that all components of the program unit have the desired output results, so that all features can run well, while the sensor accuracy test results show a high degree of accuracy, so the data published by the system is valid.